Talent Management: A Critical Review Of Literature (Journal of Informatics Education and Research, 2025)
In contemporary times talent is  extremely crucial for sustenance of organisational success .The hiring of right talented employees is equally important in the organisation and to retain and reward them who bring value to the table. A talented workforce is the backbone of every successful organisation.This study focuses on the various literature review of talent management in the context of different organizations.Talent Management (TM) has become one of the  strategic topics for managers in global organizations and businesses in general. Despite the importance of talent management, researches in the area are still few, mainly conceptual research. The purpose of this article is to enhance the readers understanding of the domain of talent management concept perspectives, importance and the main practices.